African Football Migration : Aspirations, Experiences and Trajectories. - Darby, Paul.; Esson, James; Ungruhe, Christian (Manchester : Manchester University Press, 2022)
African football migration offers essential coverage of why and how African players have become actors in the global football industry. It reveals the meanings associated with migration in post-colonial Africa, and the implications of (im)mobility for the personal and professional life trajectories of youth and young men across the continent.
Front matter -- Dedication -- Contents -- Series editor's preface -- Preface -- Acknowledgements -- Introduction -- Theorising African football migration -- The history, geography and regulation of African football migration -- 'Producing' African labour for the global football industry -- Speculation in and through football migration -- 'Becoming a somebody' through football -- Luck, sackings and involuntary immobility in football -- Navigating liminality in foreign football industries -- Hope and precarity in transnational football careers -- Post-playing-career transitions and struggles -- Conclusion -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books